Analisis Kualitas Mutu Palayanan Terhadap Kepuasan Fasilitas Kesehatan Tingkat I Pada Mahasiswa Kesehatan Masyarakat FIKKIA UNAIR - Kamila, Hikmatul; Lailiyah, Syifa'ul; Putri, Citta Nabila Rafida; Ikhsani, Liny Fasisca Nurul (Madani: Jurnal Ilmiah Multidisiplin, 2024)
The quality of health care is one of the important factors that must be considered in an effort to achieve patient satisfaction. The quality of health care can be measured through aspects of responsiveness, reliability, empathy, assurance, and physical evidence. Feelings of satisfaction in patients will affect how the loyalty of patients to health care facilities. Patient loyalty is a long-term impact of patient satisfaction that has used health services. This study aims to analyze the quality of service quality to the satisfaction of Level I health facilities in public health students FIKKIA UNAIR. Subjects in this study were public health students of FIKKIA UNAIR who had JKN and had access to FKTP services in Banyuwangi as many as 97. The research design used is crossectional research through the filling of questionnaires or questionnaires. In data analysis techniques, using GAP analysis, normality test, and wilcoxon test. This study shows that the average value of the largest GAP in the aspect of assurance (assurance) of 4.53. The average value of the lowest GAP in the aspect of physical evidence (tangiable) is 0.32. Analysis of data conducted through the Wilcoxon test showed the value of Asymmp. Sig. (2-tailed) < 0.05 then Ho is rejected so that the quality of service quality affects the satisfaction of Public Health students FIKKIA UNAIR. The conclusion that can be drawn from this study is that there is a significant gap between expectations and reality in the service of Health Facilities level I (FKTP) in Banyuwangi.